The Role Of Dakwah In Overcoming The Moral Crisis Of Youth In The Digitalization Era - Raefaldhi, Muhammad; DaniHarahap, Iyansyah Umar; Rahman, Surya; Aunila, Muhammad Haekal; Rubino, Rubino (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study aims to examine the role of Islamic da'wah in addressing the moral crisis among adolescents in the digital era. The main focus of this study is how da'wah can be an effective means of moral and spiritual development for the younger generation who are vulnerable to the negative influences of digital technology. The method used in this study is a literature study with a qualitative approach. Data were obtained from various library sources such as books, scientific journals, articles, and relevant research reports, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that Islamic da'wah plays a crucial role as a medium for conveying Islamic values, a moral bulwark against negative digital influences, a means of religious education and enlightenment, and an effective means of communication with adolescents. Da'wah utilizing digital media such as videos, podcasts, social media, and online platforms has proven more effective in reaching adolescents and shaping their moral character in accordance with Islamic values. Da'wah that is communicative, interactive, and relevant to the challenges of the times has been proven to have a positive impact on the spiritual awareness and behavior of adolescents in the digital era